Impact of Macroeconomic Policies on Sudanese Economic Growth: Empirical Evidence via Switching Regression - Arabi, Khalafalla Ahmed Mohamed (European Scientific Journal, ESJ, 2019)
This paper focuses on assessing the impact of macroeconomic policies on the expansion and contraction of Sudanese real GDP as well as the computation of the number and the expected duration of each for the period of the period 1960Q1-2017Q4. The main tools of analysis are Simple switching regression and Markov switching regression are. The unemployment growth rate is the regime-switching variable in addition to the growth rates of the nominal effective exchange rate, real money supply, current government expenditure, and development expenses as non-switching variables. Markov-switching regression also outweighs simple switching regression in terms of Akaike information criterion, and transition probabilities. Results show that monetary policy was effective between the period of 1960Q1-1976Q4 adding 1.2% of real value. This however is; contrary to the period 1977Q1-1997Q4 where 60% of real value has been lost and improved significantly in the course of 1998Q1-2017Q4, hence, missing only 1%. The effect of the unemployment rate on growth at the period of contraction is almost four-time of the expansion. The positive effect of development expenses combined with the negative impact of current expenditure on the growth rate reveals the efficacy of monetary policy over fiscal. The exchange rate operates as a shock absorber. The expected duration, and the probability of staying in contraction last more than the expansion.